Effect of nano-fibril cellulose (NFC) filler towards the swelling and diffusion behavior of superabsorbent polymer composite - Lim, B. R.; S. N. A., Mazlan; Suriati, Ghazali; Syarifah, Abd Rahim; Saidatul Shima, Jamari (IOP Publishing, 2020)
Superabsorbent polymers (SAP) exist as a three-dimensional network consisting of branched or linear chains that are chemically or physically crosslinked and possess the ability to retain large amounts of fluids. To be in coherence with the global demand for more biodegradable materials, nano-fibril cellulose (NFC) is introduced as fillers during the synthesis of SAP. The objective of this study is to investigate the effects of different amounts of NFC addition to swelling and diffusion behavior of the final product (SAP/NFC). Inverse suspension polymerization was employed to produce the NFC/SAP, in which acrylic acid (AA) was used as a monomer, acrylamide (AM) as co-monomer and N, N'-Methylenebis(acrylamide) (NNMBA) as the crosslinker. The reaction was conducted at temperature, 55°C for 3 hours. In water absorbency analysis, SAP with 0.006 wt% of NFC shows the highest water absorbency, up to 135%. Swelling kinetic study shows that all SAP exhibit second order of swelling kinetic, and obeys Fickian diffusion behavior. FTIR analysis confirmed the characteristic of SAP and the presence of NFC by identifying C=O, N-H, O=C-H, C-N, O-H, C-H, C=C, C-H, and C-OH bonds. The morphological study shows that the presence of NFC inhibits the formation of SAP in regular bead shape. In thermal stability analysis, SAP with 0.006 wt% of NFC shows the highest thermal stability compared to the other SAPs. It is concluded that the addition of 0.006 wt% NFC is the most optimum condition for cellulose-based SAP synthesis due to the highest water absorbency and thermal stability.